Leisure as a Social Right: Mapping and Challenges for Municipal Public Management in Barretos/SP - Florentino Gonçalves, Tiago; Bispo dos Santos Junior, Ailton (Revista del CLAD Reforma y Democracia, 2025)
Leisure is a constitutional social right aimed at promoting a more just, free, and solidarity-based society, grounded in human dignity. This study analyzes the role of public management in the municipality of Barretos/SP in the area of leisure, identifying the spaces and activities provided to the population, which are voluntary and non-mandatory (Dumazedier, 1979). To achieve this, data were collected from the municipal administration regarding leisure locations and activities, which were then tabulated and analyzed according to the managing body, distribution across age groups, and activity categories (sports, arts, intellectual, practical/manual, and social). It was observed that sports and social activities are distributed throughout the city, while artistic, intellectual, and practical/manual activities are more centralized, requiring public policies to expand access. It was found that, despite the existence of the Department of Sports and Leisure, other sectors also offer leisure activities. However, there is a significant need for intersectoral work to enhance and universalize this right.
Keywords: Leisure; social rights; human dignity; municipal public management; mapping